2017
DOI: 10.1080/15569527.2017.1300162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on the thickness of retinal layers in healthy smokers

Abstract: The thickness of retinal layers in healthy smokers was similar to those of healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Some have suggested that these differences were driven by thicker inner and outer nuclear layers in males 49 . While smoking has been identified as a modifiable risk factor for AMD 5,50-53 , we did not find any association between macular retinal thickness and smoking at baseline, which is also consistent with previous reports 54,55 . Once adjusted for age, baseline differences in retinal thickness among eyes with a grade 0 were driven by patients from the Chr1-prot-del group.…”
Section: Discussionsupporting
confidence: 93%
“…Some have suggested that these differences were driven by thicker inner and outer nuclear layers in males 49 . While smoking has been identified as a modifiable risk factor for AMD 5,50-53 , we did not find any association between macular retinal thickness and smoking at baseline, which is also consistent with previous reports 54,55 . Once adjusted for age, baseline differences in retinal thickness among eyes with a grade 0 were driven by patients from the Chr1-prot-del group.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a total of 13 observational studies (7 case-control, 5 cross-sectional, and 1 prospective consecutive case series study) were included [1628]. In the included studies, we identified a total of 614 smokers and 625 controls.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies on the effects of smoking on retinal vessels 73,74 , but this does not explain how they perform better than normal. Moreover, there are spectral domain optical coherence tomography studies which shows the thickness of retinal layers in healthy chronic smokers was not significantly different to those of healthy individuals 75,76 . Sex, age, and confounding factors were likely to improve predictions, in other words, a large number of men over 30 years of age were included in our study, resulting in uniform results and higher R 2 values.…”
Section: Discussionmentioning
confidence: 99%